Rectal neoplasia extending to the dentate line: clinical outcomes of endoscopic submucosal dissection. (1st November 2020) - Andrisani, Gianluca; Fukuchi, Takehide; Hassan, Cesare; Hamanaka, Jun; Antonelli, Giulio; Costamagna, Guido; Di Matteo, Francesco Maria; Hirasawa, Kingo
Abstract: Background: The European Society of Gastrointestinal Endoscopy (ESGE) and the Japan Gastroenterological Endoscopy Society (JGES) give no specific recommendations on the best treatment for colorectal neoplasia involving the dental line (DLCN). Objective: Aim of this study was to analyse efficacy and safety of Endoscopic Submucosal Dissection in the treatment of colorectal neoplasia involving the dentate line (DLCN) compared to non-DLCN. Design: Retrospective study. Patients: We retrospectively evaluated all consecutive patients undergoing ESD for rectal neoplasia at two endoscopical tertiary referral centers (Italy and Japan) from January 2008 to December 2019. Main outcome measures: Anthropometric, clinical, procedural, and follow-up data was collected, analysed, and compared between patients with DLCN and patients with non-DLCN. Results: Overall, 314 patients were enrolled (163 female, 51.9%). Mean age was 68 years (range, 32–92 years). En-bloc resection was achieved in 311/314 (99%) patients. Lesion size was higher in DLCN group than in the non-DLCN group (46.1 vs 38.9 mm; p  = .03). Submucosal invasion rate was also higher in the DLCN group (29.6 vs 18.4%, p  = .04). Procedure time was significantly longer in the DLCN group, (89.6 vs. 73.1 min; p  = .002). Hospitalization length following ESD was similar in both groups. Limitations: Retrospective study design. Conclusions: ESD seems to be safe and effective in the treatment of colorectal neoplasia involving the dentate line and can be considered the best therapeutic strategy.